DEVELOPING STUDENTS' CREATIVE SKILLS IN NATIONAL CRAFTS - Xudoyqulovna, Mukumova Feruza; Gulamjonovich, Djurayev Muzaffar; Amanturdiyevna, Radjabova Dilafruz; Almaxmatovna, Xolmurodova Saboxat (International Journal of Psychosocial Rehabilitation, 2020)
The use of modern teaching methods in teaching students the secrets of crafts is important in secondary special vocational colleges and secondary schools. Therefore, advanced pedagogical technologies for the formation of a new content of applied arts education in professional colleges, modern teaching aids, and didactic aspects of the educational process and scientific-practical issues of teaching in this field. The solution of the problem is one of the most pressing issues of today. The secrets of vocational colleges and crafts can be enhanced by using new pedagogical and problem-based teaching methods. Students will find it easier to understand lessons on a scientific basis, improve their skills in managing lesson requirements, and expand their spatial imagination.